Geriatric Conditions Are Associated With Decreased Anticoagulation Use in Long‐Term Care Residents With Atrial Fibrillation - Ning Zhang; Jay Patel; Zhiyong Chen; Yanhua Zhou; Sybil Crawford; David D. McManus; Jerry Gurwitz; Theresa I. Shireman; Alok Kapoor (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Anticoagulation is the mainstay for stroke prevention in patients with atrial fibrillation, but concerns about bleeding inhibit its use in residents of long‐term care facilities. Risk‐profiling algorithms using comorbid disease information (eg, CHADS2 and ATRIA [Anticoagulation and Risk Factors in Atrial Fibrillation]) have been available for years. In the long‐term care setting, however, providers and residents may place more value on geriatric conditions such as mobility impairment, activities of daily living dependency, cognitive impairment, low body mass index, weight loss, and fall history. Methods and Results Using a retrospective cohort design, we measured the association between geriatric conditions and anticoagulation use and type. After merging nursing home assessments containing information about geriatric conditions (Minimum Data Set 2015) with Medicare Part A 2014 to 2015 claims and prescription claims (Medicare Part D) 2015 to 2016, we identified 228 741 residents with atrial fibrillation and elevated stroke risk (CHA2DS2‐VASc score ≥2) for our main analysis. Recent fall, activities of daily living dependency, moderate and severe cognitive impairment, low body mass index, and unintentional weight loss were all associated with lower anticoagulation use even after adjustment for multiple predictors of stroke and bleeding (odds ratios ranging from 0.51 to 0.91). Residents with recent fall, low body mass index, and unintentional weight loss were more likely to be using a direct oral anticoagulant, although the magnitude of this effect was smaller. Conclusions Geriatric conditions were associated with lower anticoagulation use. Preventing stroke in these residents with potential for further physical and cognitive impairment would appear to be of paramount significance, although the net benefit of anticoagulation in these individuals warrants further research.